Analisis Regresi Logistik Biner pada Faktor-Faktor yang Mempengaruhi Kemiskinan di Provinsi Jawa Timur - Kholishah Isnaini; Laelatul Khikmah (Jambura Journal of Probability and Statistics, 2025)
Poverty is a major challenge facing society and it contributes to the low rate of economic growth and inadequate quality of life. Indonesia has a relatively high percentage of poor people, largely due to its large population. East Java Province ranks third in terms of the highest poverty rate in Java. Poverty in East Java Province in 2019 until 2023 is in a phase of fluctuation that is not balanced by equal distribution of population and increased employment opportunities in East Java Province. This study aims to determine the factors that influence the poverty rate in the region and will also evaluate the extent to which the resulting model is effective in measuring poverty trends in East Java. The results show that the variable of expected years of schooling has an effect on poverty in East Java. Thus, every one-year increase in expected years of schooling can reduce the chance of a person experiencing poverty by 98.3%. Therefore, education has an important role in reducing poverty